Assessing potential for heavy metal phytoremediation in Clinacanthus nutans - Mohd Sapri, Nurul Aisyah (2018)
Heavy metals pollution on soil derived from population growth and industrialization poses serious threat to the living things. Phytoremediation which is plant based soil remediation is preferable due to effective cost and minimal side effect on the environment. The objectives of this study were to determine the effectiveness of Clinacanthus nutans in removing heavy metal in contaminated soil and to evaluate uptake and translocation of heavy metal in plant parts especially in root, stem and leaves. Clinacanthus nutans were planted on ten different treatments level of growth media – T0 control (1 kg soil), T1 (1 kg soil + 100 ppm CuSO4), T2 (1 kg soil + 200 ppm CuSO4), T3 (1 kg soil + 300 ppm CuSO4),T4 (1 kg soil + 100 ppm FeSO4),T5 (1 kg soil + 200 ppm FeSO4), T6 (1 kg soil + 300 ppm FeSO4),T7 (1 kg soil + 100 ppm ZnSO4),T8 (1 kg soil + 200 ppm ZnSO4), and T9 (1 kg soil + 300 ppm ZnSO4). Plant height and number of leaves were recorded every two week. Plant biomass was measured according to plant parts (leaves, stems, roots) and heavy metal concentrations of plant and soil samples were analysed using Atomic Absorption Spectrophotometry (AAS). Heavy metal concentrations of Cu, Fe and Zn in growth medium after harvest were ranged from 0.23 to 2.19, 579.55 to 697.45 and 2.26 to 28.55 mg/kg, respectively. Among the plant parts, roots of Clinacanthus nutans were the most efficient plant parts that capable to accumulate Cu, Fe and Zn. The highest Cu concentrations in plant parts found in T3 with value 3.29 mg/kg, while for Fe and Zn, the highest concentrations was recorded in T6 and T9 with value 1008.97 mg/kg and 41.38 mg/kg, respectively. Bioconcentration factor (BCF) and Translocation factor (TF) of Cu, Fe and Zn showed that BCF value was lower than 1 while TF value was greater than 1 indicating that Clinacanthus nutans is capable to translocate metals from roots to shoots and this study confirms that this species as a phytoextractor plant.